UPAYA MENINGKATKAN HASIL BELAJAR SISWA KELAS XII IPS-1 PADA MATERI TEKS DISCUSSION PELAJARAN BAHASA INGGRIS MELALUI MODEL PEMBELAJARAN FOCUS GROUP DISCUSSION DI SMA NEGERI 1 KEMBANG TANJONG KABUPATEN PIDIE - Yusmadaniar Yusmadaniar (Jurnal Real Riset, 2022)
This study aims to examine the effectiveness of the Focus Group Discussion Method on increasing students' learning motivation in the field of English studies. The subjects of this study were class XII students for the academic year 2020-2021. There are 25 students, consisting of 13 male students and 12 female students. This research took place in two cycles, each cycle consisted of; “planning, action, observation and reflection. The data collected in this study include: student learning outcomes, observations of activities during learning, post-test results given and reflections from reflection quiz sheets. Observation of teacher performance in learning by using Focus Group Discussion method and reflection from research partners, taken at the end of each cycle. The results of the research in cycles 1 and 2 are 1.) Teacher activity has increased well, namely achieving (standard score